2010
DOI: 10.3354/cr00937
|View full text |Cite
|
Sign up to set email alerts
|

Precipitation trends in Spanish hydrological divisions, 1946–2005

Abstract: This paper presents an analysis of precipitation changes in the main Hydrological Divisions (HDs; 'Cuencas Hidrográficas', Water Planning Divisions) in Spain from . Trend analysis revealed several monthly long-term variations and important spatial differences that should be taken into account for any national water-planning scheme. The most spatially coherent signals were a negative trend observed in March and June, affecting all catchments (HDs), and a positive trend in October, which was particularly evident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
32
0
4

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 48 publications
4
32
0
4
Order By: Relevance
“…Changes in the precipitation patterns in the same area have also been identified (Esteban-Parra et al, 1998;Millán et al, 2005;Muñoz-Díaz and Rodrigo, 2006;Estrela et al, 2010;Gonzalez-Hidalgo et al, 2010;Gallego et al, 2011).…”
Section: Introductionmentioning
confidence: 83%
“…Changes in the precipitation patterns in the same area have also been identified (Esteban-Parra et al, 1998;Millán et al, 2005;Muñoz-Díaz and Rodrigo, 2006;Estrela et al, 2010;Gonzalez-Hidalgo et al, 2010;Gallego et al, 2011).…”
Section: Introductionmentioning
confidence: 83%
“…Casi el 60% de los aforos analizados tienen coeficiente por debajo de 12 y el 50% inferior a 8. Esta irregularidad de las aportaciones anuales tiene una enorme relación con el ritmo y la propia irregularidad de las precipitaciones anuales (González-Hidalgo et al, 2010;Cortesi et al, 2014;Serrano-Notivoli et al, 2017). Esta correspondencia es muy directa en los tramos altos de las cuencas y se puede ir desdibujando en aquellos ríos que reciben una mayor cantidad de afluentes de entidad.…”
Section: Determinación De La Irregularidad: Valores De Coeficiente Deunclassified
“…Different studies carried out in the Mediterranean region suggest that notable changes in seasonal precipitation regimes occurred during the second half of the twentieth century. For example, in Spain, González-Hidalgo et al (2010) and Ramos et al (2012) observed changes affecting the main rainy seasons, with a negative trend in spring (between March and June in all Spanish basins) and a positive one in October. In an analysis carried out for the period 1901-2008 in France, Hirschi and Seneviratne (2010) observed a decreasing trend in spring-to-autumn correlations.…”
Section: Introductionmentioning
confidence: 96%